Baśń o Erosie i Psyche Apulejusza z Madaury. Duchowe aspekty baśni - Pawłowski, Kazimierz (Vox Patrum, 2016)
This work will discuss the eponymous tale of „Cupid and Psyche”, originally written as a part of Lucius Apuleius Madaurensis’ „Metamorphoses”. The tale’s main thread, the motif of Psyche making an effort to reclaim Cupid’s lost affection, is depicted through the means of mysteriosophic context of Apuleius’ philosophy, as well as his theory on love. The work will draw upon the characteristic motifs of the ancient sacred mysteries, thus suggesting that the story of Psyche’s trials and tribulations is somewhat an allegory of the spiritual development of man, who searches for love to find the meaning of his life and the fulfillment of his spiritual yearning for the eternal and the divine.